2013
DOI: 10.1111/crj.12074
|View full text |Cite
|
Sign up to set email alerts
|

The effect of rehabilitation on health‐care utilisation in COPD patients in Copenhagen

Abstract: The study provides the policy decision makers in the Municipality of Copenhagen with an assessment of the effect of a real-life intervention. It shows that the pulmonary rehabilitation programme introduced had the anticipated effects on health-care utilisation. The study also suggests that the methods used for evaluation were appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
3
1
Order By: Relevance
“…This finding is in accordance with (Abedi, Salimi, Feizi, & Safari,, 2013) who found that the majority of the studied patients were married. This finding is in contrast with (Jacobsen, Rusch, Andersen, Adams, Jensen, & Frølich, 2014) who stated that more than two thirds of the patients were single.…”
Section: Raycontrasting
confidence: 77%
“…This finding is in accordance with (Abedi, Salimi, Feizi, & Safari,, 2013) who found that the majority of the studied patients were married. This finding is in contrast with (Jacobsen, Rusch, Andersen, Adams, Jensen, & Frølich, 2014) who stated that more than two thirds of the patients were single.…”
Section: Raycontrasting
confidence: 77%
“…Furthermore, 63.9% of the respondents had acute hospital admissions because of COPD complications in the previous year. Rehabilitation and self-management education can reduce hospital admissions and number of bed days 1,8. The reported low frequency of offers of pulmonary rehabilitation, COPD self-management education, and GP COPD consultations in this cohort indicates that offers of these health care services are untapped resources for this group, despite being services with the potential to reduce hospital admissions1,8 and improve self-management activation and quality of life for persons living with COPD 9,26…”
Section: Discussionmentioning
confidence: 86%
“…Each of the three integrated care approaches was subject to a series of evaluations and these have shown evidence of improvements on a number of process and outcome measures, as well as selected utilisation measures. These include significant improvements on a number of intermediate outcomes such as glycaemic control, blood pressure, or body weight among patients with diabetes 21 and significantly smaller increases in the number of hospital admissions, bed days, and outpatient visits over a two year period among people with COPD in the SIKS project 22 ; improvements in process measures such as guideline adherence, measures of health care utilisation, health outcomes such as a reduction in the prevalence of fractures sustained by people with osteoporosis, a reduction in the proportion of people requiring long-term care and a reduction in number of potential years of life lost in the intervention group, measures of patient satisfaction, and costs measured as relative cost savings in the Gesundes Kinzigtal 5,23 ; or the cost-effective delivery of integrated diabetes care 24 and clinically relevant improvements among patients with poorly controlled diabetes in the Maastricht programme. 25 However, in addition to the direct impacts on service and patient outcomes, individual care models had important wider impacts.…”
Section: Outcomes and Impactsmentioning
confidence: 99%